Elimination of falciparum malaria from Sri Lanka: an epidemiological possibility? - A. R. Wickremasinghe; D. R. Wickremasinghe; G. Galappaththy; D. M. Gunawardena (College of Community Physicians of Sri Lanka, 1999)
No abstract available